Relationships between maternal attachment and Malaysian adolescents’ social responsibility with authoritative parenting as mediator - Ng, Yi Ming (2015)
Malaysia is a multiracial society where the blend of different traditions and cultural heritage has produced its diverse cuisine. Diversity of Malaysian foods has great potential to attract international tourists who seek culinary pleasures which can place Malaysia as a food tourism destination. However, Malaysian food seems to have been ignored in the tourism industry and food does not play an important role in attracting tourist to visit Malaysia as compared to its neighboring countries like Thailand and Singapore. This might be due to the lack of efficient marketing strategies and tools including the lack of studies that investigate the marketing mix efficiency in developing international tourism interest in Malaysian food and cuisines. In addition, there has been little study about Malaysian food and possible impact of food on the tourism industry. As such, the present study has developed a conceptual framework to address this gap. The objectives of this study are to (1) examine the relationship between marketing mix (food quality, price, location, promotion, physical environment, employees and process) and tourist satisfaction toward Malaysian food; (2) investigate the relationship between tourist food satisfaction and their behavioral intentions, and (3) determine the moderating role of destination image in the relationship between tourist food satisfaction and behavioral intentions. The targeted population of this study was international tourists, who visited tourist attraction areas in Kuala Lumpur and Selangor during the survey period. The collected data were statistically analyzed using SPSS 21 and AMOS 21. The findings of this study support the hypothesized relationships proposed in the theoretical model. Specifically, the result of Structural Equation Model revealed that there is a relationship between marketing mix and tourist satisfaction toward Malaysian food. The result of the specific hypotheses tests regarding the association between marketing mix elements and tourist food satisfaction showed that only three elements (food quality, price, and physical environment) have a significant relationship with tourist food satisfaction. The result also showed that tourist food satisfaction is significantly related to their behavioral intentions. In addition, based on the results of the multiple group analysis by SEM, it was found that destination image moderates the relationship between tourist food satisfaction and behavioral intentions. This study has contributed new knowledge about the relationship between marketing mix and tourist satisfaction and behavioral intentions in food context. The study also provides a contribution to the literature regarding the moderating effect of destination image on the relationship between tourist food satisfaction and behavioral intentions. The study will benefit the destination marketers, especially restaurant operators in understanding what tourists want and need. Findings from this study provide guidance to design effective marketing strategies to increase tourist food satisfaction as well as to influence current tourists' intentions to return and recommend Malaysian food to others.